Identifying Innovation Drivers in Indonesiaís Tourism Supply Chain: An Exploratory Factor Analysis - Irawan, Herry; Fernando, Yudi; Windya Giri, Refi Rifaldi (Atlantis Press, 2024)
Introduction/Main Objective: This study investigates the drivers of supply chain innovation capability within Indonesia's tourism industry, emphasizing strategic partnerships, process innovation, and responsiveness. Background of the Problem: The tourism industry significantly contributes to Indonesia's GDP and employment but faces challenges such as infrastructure limitations, environmental concerns, and competition. Previous research highlights the importance of innovation in improving supply chain efficiency, yet there is a gap in understanding specific innovation drivers in developing economies like Indonesia. Research Gaps/Novelty: This study addresses the gap by exploring the drivers of supply chain innovation in Indonesia's tourism sector. The novelty lies in the detailed examination of strategic partnerships, process innovations, and responsiveness through exploratory factor analysis (EFA). Research Methods: Data were collected through a survey of 130 tourism professionals across various managerial levels in Indonesia. EFA was used to identify the underlying factors influencing supply chain innovation. The datasetís suitability for factor analysis was validated using the Kaiser-Meyer-Olkin (KMO) measure and Bartlettís test of sphericity. Findings/Results: Results indicate that strategic partnerships enhance resource utilization and knowledge sharing, process innovations improve workflows and customer satisfaction, and responsiveness to market changes is crucial for competitiveness. These findings provide actionable insights for stakeholders to enhance innovation capabilities. Conclusions and Implications: This study underscores the necessity for continuous innovation and strategic adaptability to ensure the sustainable development and competitiveness of Indonesia's tourism industry. The findings offer practical strategies for enhancing service delivery, operational efficiency, and responsiveness, supporting resilience and alignment with global sustainable tourism practices.